Impact of the Critical Success Factors on International Development Projects in Mukalla, Yemen - Al-Nasi, Saleh Mohammed Mubarak Al-Bakri; Ismail, Sushilawati; Yunus, Riduan (Advances in Social Sciences Research Journal, 2025)
The finance of International Development Projects in Yemen using Social Fund for Development (SFD), is bedeviled by a number of impediments. This study identified and measured the critical success factors in International Development Projects. The approach is quantitative; data was collected using 338 structured, closed-ended questionnaires. Relative Importance Index (RII) and PLS- SEM was used in the analysis. The findings revealed that: Project Planning and Execution, Construction Organizational Factors, Client and Stakeholder Engagement and Environmental Factors were identified as the most critical success factors. The Environmental Factors with (β = 0.410, t = 6.013, p < 0.05) accounted for the highest variation, while Project Planning and Execution with (β = 0.184, t = 3.664, p < 0.05) has the second highest prediction on the success of development projects in Yemen. The four exogenous variables predicted about 52% of the variation in the success in International Development Projects. It was recommended that environmental issues like political, economic, social, project location and size; and then project planning and execution issues like plan formulation, risk assessment and mitigation, monitoring, and commitment to meet quality, cost and time objectives deserve special attention.